Older adults' community participation, physical activity, and social interactions during and following COVID-19 restrictions in Australia: a mixed methods approach - Claire Gough; Chris Barr; Lucy K Lewis; Claire Hutchinson; Anthony Maeder; Stacey George (BMC, 2023)
Abstract Background With the increasing age of the global population, key components of healthy ageing including community, physical, and social participation continue to gain traction. However, management of the COVID-19 pandemic aimed to protect older adults and reduce the spread of the virus, this restricted community participation and reduced the opportunities for social interaction. Methods This mixed methods study investigates community dwelling older adults' community participation; physical activity and social interaction prior to, during, and following the COVID-19 lockdown in Adelaide, Australia. Twenty-six community dwelling older adults were monitored over three time-points between November 2018 and October 2020, with Global Positioning Systems, accelerometry and self-reported diaries. In addition, nineteen participants completed semi-structured interviews. Results Community participation varied across the three time points, with significant reduction in the number of trips taken out-of-home (p = 0.021), social interactions (p = 0.001) and sleep quality (p = 0.008) during restrictions. Five themes were identified to explain personal experiences of community participation during restrictions: (1) Reframing of meaning, (2) Redefining to maintain activities, (3) Revision of risk, (4) Reflection and renewal and (5) Future planning. Conclusion During COVID-19 the physical and social activities of community dwelling older adults changed. Services that support older adults to adapt their activities   , considering their capacities and preferences, to facilitate community participation are required.